Procedure Skills of Differential Calculus in High School (Docentes 2.0 Journal, 2021)
Upper secondary education in Mexico is of vital importance because the student consolidates their knowledge in selecting studies towards higher education. The physical-mathematical area includes the subject of differential calculus, with a high level of demand due to the complexity of other mathematics concepts such as variation and representation of mathematical models within the study of functions. The present proposal consisted of analyzing the procedural skills developed by students at the upper secondary level when solving limits and derivation exercises and applying knowledge in specific situations. In this research, a quantitative approach was used, involving a questionnaire to analyze the performance of differential calculus students when solving both exercises and contextualized problems. The study was carried out with a population of 40 high school students. In this way, it was determined whether the young people could travel, both at the basic levels such as identity, solve, and at those higher levels such as interpret or explain, the latter being the necessary parameters within the high school graduation profile.
Keywords: Differential Calculus; Procedural Skills; Baccalaureate